Al-Arqam & ajaran aurad Muhammadiah : satu penilaian - Farahwahida Mohd Yusof (Penerbit Universiti Teknologi Malaysia, 2007)
On Darul Arqam, an Islamic fundamentalist organization banned in Malaysia and its controversial doctrine of Islamic teachings